2020
DOI: 10.1096/fba.2020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Depleting interferon regulatory factor‐1(IRF‐1) with CRISPR/Cas9 attenuates inducible oxidative metabolism without affecting RA‐induced differentiation in HL‐60 human AML cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The CD11b and NUMB knockout cell lines were constructed as previously described with CRISPR/Cas9 [35]. The sequence for CD11b sgRNA is Forward: 5-CAC CGA CCT TCC AAG AGA ACG CAA G-3; Reverse: 5-AAA CCT TGC GTT CTC TTG GAA GGT C-3.…”
Section: Construction Of Crispr-mediated Stable Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD11b and NUMB knockout cell lines were constructed as previously described with CRISPR/Cas9 [35]. The sequence for CD11b sgRNA is Forward: 5-CAC CGA CCT TCC AAG AGA ACG CAA G-3; Reverse: 5-AAA CCT TGC GTT CTC TTG GAA GGT C-3.…”
Section: Construction Of Crispr-mediated Stable Cell Linesmentioning
confidence: 99%
“…The sequence for Numb sgRNA is Forward : 5-CAC CGG ATG AAG AAG GCG TTC GCA C-3; Reverse: 5-AAA CGT GCG AAC GCC TTC TTC ATC C-3. The sg-NC control cell was the one used in our previous report [35].…”
Section: Construction Of Crispr-mediated Stable Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR/Cas9 technology allowed the excision of the interferon regulatory factor-1 (IRF-1) gene from HL-60 cells. Thus, it was found that IRF-1 is not essential for differentiation induced by all-transretinoic acid or 1,25-Dihydroxyvitamin D3, but is involved in the upregulation of p47phox expression required for mature-cell ROS production in granulocyte metabolism 18 .…”
Section: Fbxo1allows the Progression Of Mds To Aml 8 2 Bend3mentioning
confidence: 99%